HUBUNGAN INTERAKSI SOSIAL DENGAN KESEPIAN PADA LANJUT USIA - Muhajir Sulton Shobri, Muhammad; Ma’rifatul Azizah, Lilik (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Loneliness is the result of interaction with other individuals who are not in accordance with what was expected earlier. While loneliness is a high or low range of subjective feelings of individuals in the form of negative feelings such as feelings of alienation, lack of closeness with others (Herliawati et al, 2012).This research used cross sectional design. The sample in this research is the number of elderly people 60-74 years old, 53 using simple random sampling method. The independent variables in this researchis social interaction and the dependent variable in this research is lonely. Social interaction is measured with a check list of social interaction while loneliness is measured with a check list of loneliness modified from UCLA Loneliness Scale Version 3. The results show that social interaction and lonely in the village districts prupuh panceng gresik district has a value of ρ = 0.00 <α 0:05 means H0 rejected and H1 accepted that there is a relationship of social interaction with the loneliness of the elderly in villages prupuh Gresik. The research usedanalyzed by chi-square test Nominal Nominal contingency coefficient with significant level of 0.05. Chi Square test results by Nominal Nominal contingency coefficient shows that there is a significant relationship between social interaction with loneliness in the elderly with Pearson Chi-Square Asymptotic Significance (2-sided) Approximate Significance .000 and .000 with a negative direction.When elderly people who have poor social interaction, the more they will feel lonely elderly. Elderly can increase social interaction with the surrounding environment as active in environmental activities, and lectures, so that the elderly do not feel lonely.Keywords: Elderly, Social Interaction, Loneliness